Strategic Planning and Competitiveness in Interprovincial Ground Transportation Companies Based in Lima, 2022 - Gargate Obregón, Samuel (2023)
This research study aims to determine strategic planning and its relationship with competitiveness in interprovincial ground transportation companies based in Lima, 2021. A quantitative, non-experimental and correlational research methodology was used, describing in detail the direct actions of the companies in relation to their planning. The population was comprised of 485 transportation companies in Metropolitan Lima, and 87 of them served as the representative sample. From the results, it was observed that values, mission and vision do not contribute to the companies’ competitiveness. Therefore, it is concluded that planning does not increase competitiveness. Interprovincial ground transportation companies should invest in the transportation system focusing their attention on its entire value chain.